AKTIVITAS ANTIBAKTERI EKSTRAK BUAH MAHKOTA DEWA (Phaleria macrocarpa) TERHADAP Staphylococcus aureus - Mochammad Taha Ma’ruf; Setiawan Setiawan; Bayu Prayoga Deta Putra (Interdental: Jurnal Kedokteran Gigi, 2017)
Tooth extraction though always not cause problems, but can cause some complications, one of which is endocarditis infection. The infection is caused by Staphylococcus aureus that causes abnormalities of the heart valves. The use of herbal ingredients to be an alternative to antibacterial bacteria as a result of increased resistance to antibiotics. Mahkota Dewa fruit (Phaleria macrocarpa) was selected as an antibacterial because it is active substances contains such as alkaloids, saponins, flavonoids, and polyphenols. The purpose of this study was to determine the effective concentration of the extract Mahkota Dewa fruit as an antibacterial against Staphylococcus aureus that can be made of a product in the form of a gel that can be applied to a tooth extraction wound to prevent endocarditis infection. The study is in vitro an experimental laboratory approaches Post test Only Control Group Design. Samples are distinguished by the concentration differences of the Mahkota Dewa fruit extract are 60%, 70%, 80%, 90% and 100%. The results showed that the Mahkota Dewa fruit extract concentration of 70% effective as an antibacterial against Staphylococcus aureus. The effectiveness of the extract Phaleria influenced by the ability of the active substance content of flavonoids lysis of bacterial cells.